Seismic evaluation of environmentally degraded FRP-strengthened masonry walls - Ghiassi, Bahman (2015)
Fiber Reinforced Polymers (FRPs) have been extensively used for externally bonded reinforcement of masonry structures during the last years. Available information shows that FRPs can significantly improve the seismic performance of masonry elements without altering their structural mass. However, the durability and long-term performance of the strengthened elements are not clearly known yet. Recent experimental results show that environmental conditions can lead to degradation of the bond between FRP and masonry and FRP delaminations. But the effect of these local degradation mechanisms on the global structural response is not studied yet. This paper is therefore aimed at numerically investigating the effect of environmental degradation on the global performance of strengthened masonry walls. The nonlinear behavior of masonry walls strengthened with FRP composites is initially simulated with the aim of a FE package. The adopted numerical modeling strategy is verified by comparison of numerical and experimental results. The model, once validated, is used for investigating the effect of materials and bond degradation on the global behavior and failure modes of strengthened walls. The effect of strengthening scheme on the long-term performance of strengthened walls is also investigated. The degradation data are taken from experimental tests previously performed by the authors. The numerical results show that the effect of local material degradation on the global response of strengthened walls depends on the strengthening schemes, and severity of the environmental conditions. Moreover, environmental induced degradations and FRP delaminations can lead to change of expected failure modes in the strengthened elements. These observations, that are usually neglected at the design stage, can be critical in the long-term performance of strengthened structures.